Receptor Basis for Mechanisms of Development of Local Inflammation of the Gastric Mucosa in Children with Helicobacter pylori Infection - O.N. Gerasimenko (Zaslavsky O.Yu., 2013)
The article presents data on the role of factors for innate immunity recognition in the development of local inflammation of the gastric mucosa in children with Helicobacter pylori (Н.pylori) infection. The aim of the study was to investigate the role of mechanisms of H.pylori lipopolysaccharide recognition in the development of local inflammation of the gastric mucosa in children with Н.pylori infection. We observed 55 children between the ages of 10 to 16 years with chronic H.pylori-associated gastroduodenitis (28 patients, study group) and patients with chronic gastroduodenitis non-associated with H.pylori (27 children, comparison group) in the acute stage. It is shown that the basis of an infectious-inflammatory process caused by Н.pylori, and unfavorable clinical course is functional deficiency is non-specific mechanisms of protection of the gastrointestinal tract. Features of expression of Toll-like receptor 4 (TLR4) in the biopsy sample of the gastric mucosa and the protein sCD14 content in blood serum are demonstrated for children with chronic gastroduodenitis in the acute stage. It is shown that the development of chronic gastroduodenitis associated with Н.pylori in children is accompanied by increased TLR4 expression in biopsy specimens of gastric mucosa, which is a key sensor for Н.pylori lipopolysaccharide, and low levels of TLR4-accessory sCD14 protein.